The prevalence of mild cognitive impairment in Gulf War veterans: a follow-up study - Chao, Linda L.; Sullivan, Kimberly; Krengel, Maxine H.; Killiany, Ronald J.; Steele, Lea; Klimas, Nancy G.; Koo, Bang-Bong (Frontiers in Neuroscience, 2024)
Introduction: Gulf War Illness (GWI), also called Chronic Multisymptom Illness (CMI), is a multifaceted condition that plagues an estimated 250,000 Gulf War (GW) veterans. Symptoms of GWI/CMI include fatigue, pain and cognitive dysfunction. We previously reported that 12% of a convenience sample of middle aged (median age 52 years) GW veterans met criteria for Mild Cognitive Impairment (MCI), a clinical syndrome most prevalent in older adults (e.g., > 70 years). The current study sought to replicate and extend this finding.Methods: We used the actuarial neuropsychological criteria and the Montreal Cognitive Assessment (MoCA) to assess the cognitive status of 952 GW veterans. We also examined regional brain volumes in a subset of GW veterans (n=368) who had 3 Tesla magnetic resonance images (MRIs).Results: We replicated our previous finding of a greater than 10% rate of MCI in four additional cohorts of GW veterans. In the combined sample of 952 GW veterans (median age 51 years at time of cognitive testing), 17% met criteria for MCI. Veterans classified as MCI were more likely to have CMI, history of depression, and prolonged (> 31 days) deployment-related exposures to smoke from oil well fires and chemical nerve agents compared to veterans with unimpaired and intermediate cognitive status. We also replicated our previous finding of hippocampal atrophy in veterans with MCI, and found significant group differences in lateral ventricle volumes.Discussion: Because MCI increases the risk for late-life dementia and impacts quality of life, it may be prudent to counsel GW veterans with cognitive dysfunction, CMI, history of depression, and high levels of exposures to deployment-related toxicants to adopt lifestyle habits that have been associated with lowering dementia risk. With the FDA's recent approval of and the VA's decision to cover the cost for anti-amyloid β (Aβ) therapies, a logical next step for this research is to determine if GW veterans with MCI have elevated Aβ in their brains.